More Reasons for Reading Carrie Dobbs, Frank Dobbs - Dobbs C.; Dobbs F. (New Jerrsey Prentice Hall Regents, 1992)
This reading skills book is designed to build a non-technical vocabulary and reading skills suitable for advanced study, introducing students to complex syntax. Each of the 15 chapters contains pre-reading discussion, a reading selection, skills exercises and writing tasks.
Keywords: 811.111